Support for Gender Stereotypes: Does Madrasah Education Matter? - Asadullah, M. Niaz; Amin, Sajeda; Chaudhury, Nazmul (Taylor & Francis, 2019)
This paper examines the influence of the institutional nature of schools on gender stereotyping by exploring contrasts between non-religious and Islamic faith (that is madrasah) schools among secondary school-going adolescents in rural Bangladesh. In particular, differences in gender attitudes across school types are explored to elucidate what about schools matters. Using a uniquely designed survey to assess the influence of school type on student characteristics, we find large differences in stereotypical gender attitudes by school type and student gender. Madrasah students in general, and unrecognised madrasah students in particular, show unfavourable attitudes about women and their abilities compared to their peers in non-religious schools. However, these differences are diminished considerably in ordered probit models suggesting that school-level differences are explained by teacher characteristics such as the nature of teacher training and average family size of teachers. These estimated effects are robust to conditioning on a rich set of family characteristics.